Is Pain Stronger in Adults or in Adolescents During Semi-Rapid Maxillary Expansion (SRME) and Fixed Appliance (FA) Therapies? - Małgorzata Kuc-Michalska; Magdalena Pokucińska; Joanna Janiszewska-Olszowska (Applied Sciences)
Rapid or semi-rapid maxillary expansion is a well-established method of treating severe transversal maxillary deficiency or transversal dental arch discrepancy. Pain is considered an inevitable undesirable adverse effect of orthodontic treatment. The aim of the present study was to compare pain levels experienced from the semi-RME (SRME) procedure between adults and adolescents and the lower fixed appliance (FA) procedure in the same patients. The study comprised 95 patients (51 adults and 44 adolescents) treated with a bonded acrylic Hass-type expander and the following month (after blocking the screw) with a lower fixed orthodontic appliance. Pain was assessed using a numerical rating scale from 0 to 10. During screw activation, adolescent patients reported a statistically significantly higher median pain level (5.00) compared to adults (3.00) [p = 0.009]. During the fixed appliance treatment, adolescent patients reported similar pain level to adults (4.5 and 4.0, respectively; p = 0.49). Interestingly, the median pain level for SRME in the whole group was 4, and was not different from the fixed appliance treatment sensations. Adolescent females had the highest pain sensation, while adult males had the lowest during both procedures, SRME and FA. The difference between the midpalatal suture opening (appearance of diastema) in adolescents (81.82%) vs. adults (64.71%) was not statistically significant (p = 0.062). The oldest patients with diastema were a 36y-2mo-old man and a 42-year-old woman, whereas the youngest patients without diastema were an 11y-11mo-old girl and a 13y-2mo-old boy. Moreover, all female patients between 30 to 42 years of age (eight women) had presented with diastema. In both age groups, the biggest disadvantage during SRME, reported by 50.53% of all patients (45.45% of adolescents and 54.9% of adults; p = 0.062), were speech problems, whereas only 18.95% of the total group (27.27% of adolescents vs. 11.76% of adults; p = 0.054) considered pain as the main disadvantage. During FA therapy, 32.63% of all patients reported pressure sores as the main disadvantage (29.55% of adolescents and 35.29% of adults; p = 0.551).